KONSEP MANAJEMEN KEUANGAN DALAM LEMBAGA PENDIDIKAN ISLAM PERSPEKTIF AL QUR’AN DAN HADIS - Iffatun Najihah; Suaib H. Muhammad (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: The Concept of Financial Management in Islamic Educational Institutions from the Perspective of the Qur'an and HadithThe background of the research is the importance of financial management in an institution, including institution of Islamic education. The purpose of this study is knowing the concept of financial management of Islamic education, analyzing the concept of Islamic education financial management perspective the Qur'an and hadith. Descriptive-qualitative is a method used in this research is. This research is a library research, which the author collects data from references such as journals, articles, books, and others. The author used primary data which took form of the Qur'an and hadith. The secondary data used by the author are books, journals, and articles. The author used a reading and note-taking technique. In analyzing the data, the author uses Miles and Huberman's perspective analysis techniques, namely: 1) data reduction, presenting data, and drawing conclusions. The results of this article are: 1) the concept of financial management has been described in detail in the Qur'an. So it is appropriate in the implementation of financial management must always be guided by what has been explained by the Qur'an 2) responsibility in managing education finances is not only faced with relationships with humans, but is also required to be held accountable to Allah SWT. Therefore, financial managers must understand the science of financial management based on the Qur'an. Abstrak: Konsep Manajemen Keuangan dalam Lembaga Pendidikan Islam Perspektif Al-Qur’an dan HadisPenelitian ini dilatarbelakangi oleh pentingnya manajemen pembiayaan dalam sebuah lembaga, termasuk lembaga pendidikan Islam. Penelitian ini bertujuan untuk menganalisa konsep manajemen keuangan pendidikan Islam dalam perspektif al Qur’an dan hadis. Metode deskriptif-kualitatif adalah metode yang digunakan dalam penelitian ini. Adapun penelitian ini merupakan penelitian pustaka, yakni penulis menghimpun data dari berbagai referensi seperti buku, jurnal, artikel, dan lain-lain. Penulis menggunakan sumber data primer berupa al-Qur’an dan hadis. Selain itu, penulis menggunakan data sekunder seperti buku, jurnal, dan artikel. Pengumpulan data dengan teknik baca catat adalah teknik yang digunakan penulis. Dalam analisis data, penulis menggunakan teknik analisis perspektif Miles dan Huberman, yaitu: reduksi data, penyajian data, dan penarikan kesimpulan. Adapun hasil dari artikel ini adalah: 1) al-Qur’an telah menjelaskan konsep manajemen keuangan secara rinci. Maka sudah sepatutnya dalam pelaksanaan manajemen keuangan harus selalu berpedoman pada apa yang telah dijelaskan oleh al-Qur’n; 2) pertanggungjawaban dalam mengelola keuangan pendidikan tidak hanya dihadapkan pada hubungan dengan manusia saja, akan tetapi juga dituntut pertanggungjawabannya di hadapan Allah SWT. Oleh karena itu, dibutuhkan pengelola keuangan yang memahami ilmu manajemen keuangan yang berbasis al-Qur’an.